A portable signal-on self-powered aptasensor for ultrasensitive detection of sulfadimethoxine based on dual amplification of a capacitor and biphotoelectrodes. Issue 30 (17th March 2021) - Chen, Yingxu; Gao, Jie; Yao, Xiaoling; Yan, Kai; Zhang, Jingdong
Abstract : A portable self-powered sensor is constructed for on-site detection of sulfadimethoxine with high sensitivity improved by biphotoelectrodes and a capacitor. Abstract : A one-compartment photofuel cell with two photoelectrodes was combined with a capacitor to develop a portable self-powered sensor for sulfadimethoxine (SDM) detection. The developed sensor was applied to the assay of SDM in veterinary drug samples with desirable accuracy and precision.